A NOTE ON THE DOL-NET FISHERY OFF JAFFRABAD (GUJARAT) WITH SPECIAL REFERENCE TO BOMBAYDUCK, FROM 1979-80 TO 1981-82 - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
An estimated catch of 17,345.6 t were landed at JafTrabad by dol nets.The bombayduck formed about 90.6% of the landings. The peak periods of abundancewere October-November (CPUE 245.0 and 216.9 kg) and May (CPUE231.4 kg). The size range of bombayduck varied between 30 mm and 375 mm.Juveniles below 210 mm were more abundant during February-May (93 7 to98.6%).The bycatch consisted of Coilia dussumeiri (2.6%), non-penaeid prawns(2.2%), penaeid prawns (0.8%), Ghol (1.7%) and Trichiums (0.7%). Considerablequantities of Pampns argenteiis (25.3 tonnes) in the size range 30 to149 mm were also landed